Insights on mental health when living with rheumatoid arthritis: a descriptive qualitative study of threads on the Reddit website - Park, Jamie Y. E. (BMC Rheumatol, 2020)
BACKGROUND: Reddit is a highly visited social news and discussion website where individuals anonymously ask questions, post opinions and share experiences, which provide a valuable pool of publicly available data. Our objective was to systematically search and analyze threads on the social news website, Reddit, to understand experiences of individuals with rheumatoid arthritis (RA) regarding their mental health. METHODS: We conducted a patient-oriented descriptive qualitative study. We identified threads from two subreddits, “r/Thritis” and “r/Rheumatoid”, using keywords such as “mood”, “mental health”, “stressed”, “depressed”, “anxious” over a 1-year period between June 2018 and June 2019. For included threads, we extracted the title, original post, and corresponding comments and responses. We applied thematic analysis using an inductive approach. RESULTS: Of 81 threads identified, we included 27. We identified four themes: 1) Navigating the management of RA explores how the physical impacts of the disease, lack of health resources/support and the complexity of medications affect mental health; 2) Experiencing impact on relationships and social isolation includes experiencing misconceptions of RA, feeling misunderstood and feeling guilt; 3) Experiencing loss, touches on the helplessness brought by challenges with performing self-defining activities such as self-care, work, and childbearing/parenting; and finally, 4) Experiencing emotional struggles captures how tension between fighting through and despair has led some to suicide ideation and thoughts of death. CONCLUSIONS: Online forums and communities such as Reddit have created opportunities for individuals with RA to share experiences on mental health matters, which they may not necessarily be able to share with others.